PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PT POS INDONESIA CABANG PAMULANG - Submission JORAPI; Salsha Salbila; Surti Wardani (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of service quality and price on consumer satisfaction at PT POS Indonesia Pamulang branch. The population in this study is 36,252 consumers. The sample selection in this study uses the slovin technique, which is as many as 100 consumers. The analysis methods used in this study are descriptive statistical analysis, quantitative analysis, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis test using SPSS 26 statistical data processing. The results of this study show that the service quality variable has a positive and significant effect on consumer satisfaction with a regression value of 5.905. The T-count value is 5.905 > 1.66088. The probability value of service quality was obtained with a significance value of 0.000 < 0.05. The price variable had a positive and significant effect on consumer satisfaction with a regression value of 6.979. The T-count value > the T-table was 6.979 > 1.66159. The T-count value > the T-table is 6.979 > 1.66159. The value of price probability was obtained with a significance value of 0.75 < 0.05. The variables of service quality and price had a simultaneous and significant effect on consumer satisfaction. The F-count value > F-table was 137.311 > 3.09 with a sig value from the F test of 0.000 < 0.05.